Pengaruh Lama Perkecambahan terhadap Karakteristik Fisik, Kimia dan Fungsional Tepung Kecambah Jagung Pulut (Zea mays ceratina L.) - Hartawan, Gery; Wisaniyasa, Ni Wayan; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPA, 2021)
This study aims to know the effect of time on the germinated waxy corn flour characteristics and to know which time that can produce a germinated waxy corn flour with the best characteristics. This research used a Complete Randomized Design with a different germination time as the treatment, which is 0 hour, 24 hour, 36 hour and 48 hour. The experimentation was repeated 4 times resulting 16 experimental units. The data obtained were analyzed using an analysis of variance and if the treatment had a significant effect, it was followed by a Duncan Multiple Range Test (DMRT). The results showed that the effect of time had a very significant effect on total rendement, L’ value (brightness), b’ value (green-yellow), protein content, water absorption capacity, swelling power, solubility of germinated waxy corn flour. This research also resulting a significant effect on moisture content and carbohydrate content, but resulting a non-significant effect on bulk density, a’ value (blue-red), ash content, fat content, crude fiber content and oil absorption capacity. The best characteristic of the flour in this study was the waxy corn flour that has been germinated for 48 hours with 79.44% rendement, 0.50 g/ml bulk density, L’:54.34, a’: 6.90, b’: 22,89 color, 7.15% water content, 1.56% ash content, 6.36% fat content, 9.66% protein content, 82.31% carbohydrates content, 2.39% fiber content, 1.55 ml/g water absorption, 1.81 ml/g oil absorption, 6.70 g/g swelling power, and 51.72% solubility.